Adversarial Collaboration on a Drake-S Equation for the Survival Question - Laythe, Brian; Houran, James (Journal of Scientific Exploration, 2022)
The idea of ‘life after death’ transcends philosophy or religion, as science can test predictions from claims by both its advocates and skeptics. This study therefore featured two researchers with opposite views, who jointly gathered hundreds of research studies to evaluate the maximum average percentage effect that seemingly supports (i.e., anomalous effects) or refutes (i.e., known confounds) the survival hypothesis. The mathematical analysis found that known confounds did not account for 39% of survival-related phenomena that appear to attest directly to human consciousness continuing in some form after bodily death. Thus, we concluded that popular skeptical explanations are presently insufficient to explain a sizable portion of the purported evidence in favor of survival. People with documented experiences under conditions that overcome the known confounds thus arguably meet the legal requirements for expert witness testimony. The equation that led to our verdict can also purposefully guide future research, which one day might finally resolve this enduring question scientifically. Keywords: anomalous experience, empiricism, paranormal belief, probability, survival